SCALE STRUCTURE, AGE AND GROWTH IN THE FRESHWATER CARP, LABEO CALBASU (PISCES/CYPRINIDAE) FROM HARIKE WETLAND, INDIA - Bhatia, N. K.; Dua, A. (Journal of Indian Fisheries Association, 2015)
Age structure and growth profile based on the scale studies of 468specimens ranging from 17-62 em total length of Labeo calbasu (Hamilton)from Harike wetland (30Â°13'N, 75Â° 12'E), Punjab, India have been described.the present study showed better growth in terms of two important growthparameters namely index of species average size and population weightgrowthintensity. Two distinct phases in its life history have been describedthat indicates the optimum exploitation of this species from this waterbody.Harvestable size is found to be fish of 34 em total length. The detailedstructural elaboration of scale (normal, regenerated, lateral line) has alsobeen done using scanning electron microscopy (SEM).Keywords: Scale, SEM, Age, Growth, Stock Management.